Legionella pneumophila infection of Drosophila S2 cells induces only minor changes in mitochondrial dynamics. - Elizabeth Wen Sun; Monica L Wagner; Amanda Maize; Doris Kemler; Elisabeth Garland-Kuntz; Li Xu; Zhao-Qing Luo; Peter J Hollenbeck (PLoS ONE, 2013)
During infection of cells by Legionella pneumophila, the bacterium secretes a large number of effector proteins into the host cell cytoplasm, allowing it to alter many cellular processes and make the vacuole and the host cell into more hospitable environments for bacterial replication. One major change induced by infection is the recruitment of ER-derived vesicles to the surface of the vacuole, where they fuse with the vacuole membrane and prevent it from becoming an acidified, degradative compartment. However, the recruitment of mitochondria to the region of the vacuole has also been suggested by ultrastructural studies. In order to test this idea in a controlled and quantitative experimental system, and to lay the groundwork for a genome-wide screen for factors involved in mitochondrial recruitment, we examined the behavior of mitochondria during the early stages of Legionella pneumophila infection of Drosophila S2 cells. We found that the density of mitochondria near vacuoles formed by infection with wild type Legionella was not different from that found in dotA(-) mutant-infected cells during the first 4 hours after infection. We then examined 4 parameters of mitochondrial motility in infected cells: velocity of movement, duty cycle of movement, directional persistence and net direction. In the 4 hours following infection, most of these measures were indistinguishable between wild type and dotA(-).infection. However, wild type Legionella did induce a modest shift in the velocity distribution toward faster movement compared dotA(-) infection, and a small downward shift in the duty cycle distribution. In addition, wild type infection produced mitochondrial movement that was biased in the direction of the bacterial vacuole relative to dotA-, although not enough to cause a significant accumulation within 10 um of the vacuole. We conclude that in this host cell, mitochondria are not strongly recruited to the vacuole, nor is their motility dramatically affected.